2017
DOI: 10.1111/1749-4877.12247
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acute cold exposure on oxidative balance and total antioxidant capacity in juvenile Chinese soft‐shelled turtle, Pelodiscus sinensis

Abstract: Acute cold exposure may disturb the physiological homeostasis of the body in ectotherms. To date, there has been no information on the effects of cold exposure on homeostasis of reactive oxygen species (ROS) or antioxidant defense response in the Chinese soft-shelled turtle, Pelodiscus sinensis. In this study, P. sinensis juveniles were acclimated at 28 °C, transferred to 8 °C as cold exposure for 12 h, then moved back to 28 °C rewarming for 24 h. We measured the ROS level and total antioxidant capacity (TAC) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 41 publications
1
10
0
Order By: Relevance
“…The liver is known to be a hub for metabolism, and mitochondria are considered to be the major site for cellular production of ROS (Kiss et al, 2011;Paital, 2016;Zhang et al, 2013). Results showed that both cold and heat stress can significantly increase the generation of mitochondrial ROS, which was consistent with results in other ectotherms, such as the euryhaline fish Takifugu obscurus (Cheng et al, 2015(Cheng et al, , 2017, the eurythermal bivalve Mya arenaria from a low-shore intertidal population (Abele et al, 2002) and the Chinese soft-shelled turtle Pelodiscus sinensis (Zhang et al, 2017b). To counteract the adverse effects of ROS, antioxidant enzymes can be activated to cope with oxidative stress (Cui et al, 2014).…”
Section: Discussionsupporting
confidence: 56%
“…The liver is known to be a hub for metabolism, and mitochondria are considered to be the major site for cellular production of ROS (Kiss et al, 2011;Paital, 2016;Zhang et al, 2013). Results showed that both cold and heat stress can significantly increase the generation of mitochondrial ROS, which was consistent with results in other ectotherms, such as the euryhaline fish Takifugu obscurus (Cheng et al, 2015(Cheng et al, , 2017, the eurythermal bivalve Mya arenaria from a low-shore intertidal population (Abele et al, 2002) and the Chinese soft-shelled turtle Pelodiscus sinensis (Zhang et al, 2017b). To counteract the adverse effects of ROS, antioxidant enzymes can be activated to cope with oxidative stress (Cui et al, 2014).…”
Section: Discussionsupporting
confidence: 56%
“…However, freezing can lead to physical damage, cell dehydration and whole body ischemia that can cause severe tissue damage and oxidative stress (Dinkelacker et al, 2005;Storey, 2006;Voituron et al, 2002), resulting in activation of Nrf2 and its downstream antioxidant enzymes when temperatures were reduced below 0°C. Furthermore, it has been reported that the ROS did not increase during acute cold exposure in P. sinensis (Zhang et al, 2017b), indicating a stable balance between ROS production and antioxidant defense, which indicates that cold exposure for 12 h did not produce oxidative stress sufficient to trigger Nrf2 pathway activation of antioxidant defenses.…”
Section: Discussionmentioning
confidence: 93%
“…After enduring severe cold stress, and even whole body freezing, no signs of physiological damage was detected in turtle species (Baker et al, 2007;Storey, 2006). Our previous studies of the subtropical Chinese soft-shelled turtle Pelodiscus sinensis also indicated no increase in oxidative damage after severe cold exposure (a reduction from 28°C to 8°C in less than 5 min that was then maintained for 2-12 h) (Chen et al, 2015;Zhang et al, 2017b). All these results indicate a unique ROS balancing capacity, which may promote the excellent cold stress tolerance in freshwater turtles.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…In addition, cold not only induces menstrual disorders and dysmenorrhea [5,6], it can also trigger ovarian insulin resistance, reproductive hormone disorders, and polycystic ovary phenotype [7][8][9]. Cold exposure can not only induce gynecological diseases via sympathetic neuroendocrine and endocrine systems, oxidative damage, and energy metabolism pathway [10][11][12][13], but it can also influence on reproductive system, through blood circulation changes. For instance, research by Meidan et al showed that cold stress can cause uterine artery contraction, thereby resulting in the reduction of placental blood flow [14].…”
Section: Introductionmentioning
confidence: 99%